SCREENING BACTERIAL ANTAGONISTS TO COMMON SCAB DISEASE - K. Karagoz; F. Dadasoglu; P. Mohammadi; R. Kotan (Journal of Animal and Plant Sciences, 2018)
Common scab caused by Streptomyces species is an important disease worldwide. Huge economic losses are faced because of the disease every year and control options are scant. This study was conducted to develop effective biocontrol agents, which have capability of enhancing potato yield. A total of 1048 bacterial isolates from former studies were tested against S. scabiei in-vitro and 22 out of these strains were found to be effective. Most effective four strains (KBA- 10, K-19B, TV-91C and RK-92) were chosen for field trials. All four strains can fix nitrogen and dissolve phosphate. According to the result, KBA-10, TV-91C, RK-92 and K-19B have biocontrol efficacy of 60.35%, 37.2%, 33.5% and 18.7%, respectively. They increased potato yield 40.0%, 41.1%, 25.52% and 20.42 %, respectively, compared to control. Increases provided by KBA-10, K-19B and TV-91C were found to be statistically significant. Biocontrol efficacies of K- 19B, TV-91C and RK-92 were of lesser degree, compared to KBA-10. Additionally, KBA-10 generated an extensive rise (71.7%) in tuber number. KBA-10 can be a good biocontrol agent for reducing potato scab disease and enhancing crop yield. Moreover, KBA-10 can be used in tuber seed production. al., 2010), Uruguay ( Lapaz et al., 2012), Norway (Dees
Keywords: Common scab; potato; biological control; Streptomyces scabiei.